Ethical Challenges for Patients and Healthcare Providers with the Approach to COVID-19 Context: A Review - Montazeri, Akram Sadat; Zare, Azam; Aghdam, Nasrin Fadaee; Haghighat, Sahar (West Kazakhstan Medical Journal, 2024)
Emerging diseases create ethical challenges in medical centers, so that health care providers have a moral duty to respect the rights of patients. Failure to comply with ethical principles leads to challenges and consequences that decrease patient satisfaction and reduce the quality-of-service delivery. In this review study, the published articles were retrieved using the main keywords in the databases including Medline, Web of Knowledge, Google Scholar, Scopus, and Cochrane Central Register of Controlled Trials in the Cochrane Library in 2020, and 42 articles were analyzed and reviewed. To extract the data, two researchers simultaneously reviewed and analyzed the articles. To increase the validity and reliability of the study, two researchers evaluated the quality of the articles separately. The most important challenges raised in the articles include two categories: ethical challenges of patients with emerging diseases and ethical challenges of healthcare providers with emerging diseases. It seems that in addition to dealing with the ethical needs of serving patients, dealing with issues related to the medical staff, especially the ethical aspects of their service, should also be considered. Keywords: emerging disease, COVID-19, ethical challenges, management, health care centers